Proliferation and Glia-Directed Differentiation of Neural Stem Cells in the Subventricular Zone of the Lateral Ventricle and the Migratory Pathway to the Lesions after Cortical Devascularization of Adult Rats. (11th May 2016) - Wan, Feng; Bai, Hua-Jing; Liu, Jun-Qi; Tian, Mo; Wang, Yong-Xue; Niu, Xin; Si, Yin-Chu
Abstract : We investigated the effects of cortical devascularization on the proliferation, differentiation, and migration of neural stem cells (NSCs) in the subventricular zone (SVZ) of the lateral ventricle of adult rats. 60 adult male Wistar rats were randomly divided into control group and devascularized group. At 15 and 30 days after cerebral cortices were devascularized, rats were euthanized and immunohistochemical analysis was performed. The number of PCNA-, Vimentin-, and GFAP-positive cells in the bilateral SVZ of the lateral wall and the superior wall of the lateral ventricles of 15- and 30-day devascularized groups increased significantly compared with the control group (P < 0.05 and P < 0.01 ). The area density of PCNA-, Vimentin-, and GFAP-positive cells in cortical lesions of 15- and 30-day devascularized groups increased significantly compared with the control group (P < 0.05 and P < 0.01 ). PCNA-, GFAP-, and Vimentin-positive cells in the SVZ migrated through the rostral migratory stream (RMS), and PCNA-, GFAP-, and Vimentin-positive cells from both the ipsilateral and contralateral dorsolateral SVZ (dl-SVZ) migrated into the corpus callosum (CC) and accumulated, forming a migratory pathway within the CC to the lesioned site. Our study suggested that cortical devascularization induced proliferation, glia-directed differentiation, and migration of NSCs from the SVZ through the RMS or directly to the corpus callosum and finally migrating radially to cortical lesions. This may play a significant role in neural repair.